دور محاسبة التكاليف لتحديد تكلفة الحصة التعليمية بالمؤسسة الجامعية جامعة محمد خيضر بسكرة - فريحي, محسن; بروبة, إلهام (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة الى محاولة تطبيق نظام محاسبة التكاليف على قطاع خدمة التعليم العالي في الجزائر، بالاعتماد على معلومات جامعة محمد خيضر بسكرة كعينة، وهذا لحاجتها لاتخاذ القرارات الإدارية السليمة، التي من شانها توفير الاستخدام الأمثل لمواردها مع المحافظة في الوقت نفسه على الدور الاجتماعي و الخدمي المهم المنوط إليها، حيث يعد التعليم بصفة عامة والتعليم العالي بصفة خاصة من أهم ركائز ثروة المجتمع، حيث تساهم مؤسسات التعليم العالي بدور أساسي في تعظيم القدرة المعرفية للمجتمع بحثا واستخداما وتطبيقا، من خلال ممارسة وظائفها من تدريس، وبحث علمي وخدمة المجتمع إلا أن نجاح هذه المؤسسات في إعداد رأس المال البشري المؤهل للإنتاج، وتطوير القدرات الإبداعية له، والرفع من مستوى تأهيله لتلبية مختلف حاجات المجتمع من التنمية المستدامة في جميع المجالات الاجتماعية، البشرية الاقتصادية والثقافية. This study aims to try to apply the cost accounting system to the higher education service sector in Algeria, based on the information of Mohamed Kheder University as a sample, and this is because of its need to make sound administrative decisions, which would provide the optimal use of its resources while maintaining the important social and service role assigned to it, where education in general and higher education in particular is one of the most important pillars of society's wealth, where institutions of higher education contribute a key role in maximizing cognitive ability. The society is researched, used and applied, through the exercise of its functions of teaching, scientific research and community service, but the success of these institutions in preparing human capital qualified for production, developing its creative capacities, and upgrading its qualification to meet the various needs of society for sustainable development in all social, human, economic and cultural areas.
The role of cost accounting to determine the cost of the educational session at the university institution, Muhammad Kheidar University
مقال
Keywords: محاسبة التكاليف، التعليم العالي، الحصة التعليمية.; Cost accounting, higher education.